Analysis of the structure and Mulliken charges in Tm3+-doped bismuth silicate crystals - Xuefeng Xiao; Yan Zhang; Yunlong Zhang; Yan Huang; Jiayi Chen; Han Zhang; Jiashun Si; Shuaijie Liang; Qingyan Xu; Huan Zhang; Lingling Ma; Cui Yang; et al. (Chemical Physics Impact)
In this paper, based on the first principles of density functional theory, the Materials Studio software was used to calculate and analyze the crystal structure and Mulliken charge distribution of bismuth silicate (Bi₄Si₃O₁₂, BSO) crystal doped with Tm3+ ions. The virtual crystal approximation approach was utilized to examine the impact of varying Tm3+ doping concentrations (1/12, 1/6, and 1/3) on BSO crystals. Our findings from the structural and Mulliken charge assessments reveal that a higher Tm3+ doping level can disrupt the symmetry of the crystal lattice. As the Tm3+ doping ratio rises, the Tm-O bond length initially shortens and subsequently lengthens, displaying covalent bond traits. The Tm-O bond length reaches its minimum when the Tm3+ doping ratio is set at 1/6. Concurrently, the Bi-O bond length follows a similar pattern of initial reduction followed by an increase. The Bi-O bond length is also minimized at a Tm3+ doping ratio of 1/6. This suggests that a Tm3+ doping ratio of 1/6 leads to an enhancement in the covalent character between Tm-O and Bi-O atomic pairs within the BSO crystal.